A New Species of Mites of the Genus Anystipalpus (Mesostigmata, Ascidae) from the Eastern Ukraine - Trach, V.A. (Вестник зоологии, 2012)
Anystipalpus stepposus Trach, sp. n. from Lugansk Region associated with carabid beetles is described. The new species is similar to A. livshitsi (Eidelberg, 1989), differing by the arrangement of short and thickened setae on the podonotal shield, presence of large presternal shields, shape and sclerotization of the sternal shield, shape of some setae on legs and venter of idiosoma, details of structure of the chelicerae.